Proficiency for Digital Extension Service Delivery among Public Agricultural Extension Personnel in Imo State, Nigeria - Polycarp Chika Umunakwe; Michael Chukwuneke Madukwe; Francis Chudi Anaeto; Rachel Nkeonyere Nwakwasi; Ogbonnaya Okoro Aja (Journal of Agricultural Extension)
The study examined proficiency for digital extension services delivery among public extension personnel in Imo State, Nigeria. A sample of 120 extension personnel selected from the Imo State ADP using multistage sampling procedure participated in the study. Data were collected using structured questionnaire. Data were analyzed using mean and percentages. Results showed that the extension personnel gained digital awareness from various sources. It was also found that 44.0% of the personnel were at the foundation level while 41.0% were at the intermediate level of information, data and media literacy skills, 53.0% were at the foundation level of digital communication and collaboration skills while 42.0% were at the intermediate level in digital innovation and content creation skills. Furthermore, 81.0% of the personnel were at the intermediate level in digital safety skills, 53.3% were at the foundation level in digital problem-solving and 51.0% were at the foundation level in digital learning and development. The study concluded that the personnel were proficient at digital extension services delivery however, their proficiency was still at the foundation level. The study recommended that capacity building programmes should be organized by the extension organization to raise the proficiency level of their personnel